Adventure north eaudiobook - Bloomfield, Sean (Tantor Media, 2019)
After accelerating their studies and graduating high school early, two teenagers set off from their hometown in Minnesota to embark on a 2200-mile canoe journey up the heart of North America. Their destination: the permafrost shores of Hudson Bay. Inspired by a passion for the simple life, where gadgets and schedules are replaced by nature and its harsh beauty, the duo found something that many believe is lost: a true adventure. Follow the pair up the flooding Minnesota River and through the prairie plains of North Dakota, across man-sized waves on Lake Winnipeg, and down the foaming rapids of the Canadian north. The triumphs and trials of the unforgiving wild challenged their friendship, dreams, and lives in a way that even they could have never predicted. For those who have dreamt of wilderness escape, or those who prefer to simply hear about it, Adventure North will spur the imaginative spirit and remind you that adventure is always just around the next bend.